Effect of perineal massage in the second stage of labour, on the incidence of episiotomy and perineal tears - Raja, Abinaya; P., Pallavee; Samal, Rupal (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: This study aimed to investigate whether perineal massage during second stage of labour could decrease perineal trauma in the form of episiotomy and perineal tears. Methods: One hundred and fifty term antenatal women in labour were randomly assigned to two groups, one of which received perineal massage and the other received routine care during the second stage. Frequency of episiotomies, perineal tears, intact perineums, degrees of perineal tears, duration of second stage of labour and perineal pain after 24 hours was compared. Results: Perineal massage was efficient in reducing incidence of episiotomy, duration of second stage of labour and perineal pain assessed 24 hours after delivery. The frequency of perineal tears and intact perineums did not differ significantly. Perineal massage was protective against severe form of third degree perineal tears. Conclusions: Authors suggest that perineal massage can be routinely practiced by health professionals to improve quality of life in women post vaginal delivery.